PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN CV CEMILAN GROUP INDONESIA DI SURAKARTA - Ningrum, Dewi Puji; Riska Fii Ahsani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The success of the company in achieving its goals is inseparable from the quality of human resources. Human resources with good performance will produce good performance and if the performance is poor then the organization's performance will also be poor. The purpose of this study is to analyze the effect of leadership style, work environment and work stress on employee performance. This type of survey research was conducted on employees of CV Cemilan Group Indonesia in Surakarta. The study population was 60 company employees and all of them became research samples with the census technique. Data collection used questionnaires and literature studies. Data analysis techniques used multiple linear regression, t test, F test and coefficient of determination. The classic assumption test results show that all variables have passed the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. The t test results show that leadership style has a significant effect on employee performance. The work environment has a significant effect on employee performance. Work stress has a significant effect on employee performance The results of the F test obtained a p value of 0.000 <0.05, then Ho is rejected, meaning that the model is right to be used to predict the effect of leadership style, work environment and work stress on employee performance. The results of the coefficient of determination obtained adjusted R square value of 67.6% means that the effect of leadership style, work environment and work stress on employee performance is 67.6% while 32.4% is influenced by other variables outside the research model, for example work motivation, work discipline and compensation.